Pekerja Perempuan Arena Pool Billiard di Kota Pekanbaru - Franssisca, Franssisca; Widodo, Teguh (Indonesian Journal of Education and Development Research, 2025)
Women workers are individuals who participate or rely on themselves in the informal or formal sector. One of the female workers who work in the informal sector is the billiard pool arena. Female workers tend to experience symbolic violence through the activities carried out at the billiard venue. The purpose of writing is to find out the activities of female workers in carrying out their duties. This writing is analyzed using the theory of symbolic violence developed by Pierre Bourdieu. In this writing, the technique of collecting informants uses purposive sampling technique. The subjects of the writing were 4 informants consisting of 1 administrasi , 1 menu holder, and 2 markers. Of the four informants have worked ± 6-14 months. The results of the writing state that symbolic violence occurs to female workers through activities carried out by workers. This violence has been accepted as normal and considered an obligation without any resistance.